Multi-objective optimization of a rectangular micro-channel heat sink using the augmented ε-constraint method. Issue 1 (2nd January 2020) - Tartibu Kwanda, Lagouge
ABSTRACT: This article proposes the use of an improved version of the ϵ -constraint method for the design and optimization of a rectangular micro-channel heat sink. This study aims to optimize the geometric parameters describing the micro-channel, namely its width, its fin width and its depth. The thermal resistance and the pumping power, considered as indicators of the thermal performance, have been approximated by surrogated models based on response surface approximation. The optimization task is formulated as a nonlinear programming problem. This approach has been implemented in GAMS. Sufficient details on both the single-criterion and multi-criteria formulation of the problem have been provided. The implications of the mathematical modelling formulation and the interrelationship between criteria and estimated quantities have been clarified. The use of the augmented ε-constraint method for the multi-objective optimization of a rectangular micro-channel heat sink constitutes the main contribution of this work.